"Beyond My Wildest Dreams": The Reach and Impact of Sport Education. Issue 1 (2nd January 2023) - Hastie, Peter A.; Curtner-Smith, Matthew D.; Kinchin, Gary D.; Wallhead, Tristan L.
ABSTRACT: The connection between the name "Daryl Siedentop" and the model "Sport Education" has evolved over the past three decades to become a prominent brand of physical education. This paper attempts to capture the influence of Sport Education, not only within school physical education, but in ways and arenas far beyond Daryl's original imagination. It is now used in university physical education courses and teacher preparation programs, in summer camps, and there is evidence of some use in after-school and community sports settings. This evolution has manifest pedagogical iterations of the model far beyond the essential features articulated in his initial vision, and teachers, students, prospective teachers, and coaches have all found a renewed vigor in their sport experience. The paper describes some of these "beyond" iterations of the model as a tribute to how Sport Education has served to realize multiple objectives for multiple practitioners in ways beyond his original aspirations.